Good Kings, Bloody Tyrants, and Everything In Between: Representations of the Monarchy in Post-Genocide Rwanda. (23rd April 2014) - Jessee, Erin; Watkins, Sarah E.
Abstract: Since assuming power after the 1994 genocide, President Paul Kagame and his political party, the Rwandan Patriotic Front, have struggled to unite Rwanda's citizens using, among other initiatives, a simplified version of Rwandan history to diminish the ethnic tensions that made the 1994 genocide possible. As a result, Rwanda's history has become highly politicized, with vastly divergent versions of the nation's past narrated in private settings, where it is more politically appropriate for Rwandans to share their experiences. This paper focuses on divergent representations of Rwandan monarchical figures – often unnamed – whom the narrators imbue with values according to their individual political affiliations, lived experiences, and identity. These narratives are indicative of the broader ways that modern Rwandans narrate their experiences of history in response to Rwanda's current official history, as well as previous official histories. Careful analysis reveals much about the current political climate in post-genocide Rwanda: most notably, that Rwandans continue to see their nation's past through vastly different lenses, demonstrating the enormous challenges facing the Rwandan government as it seeks to reconcile its population using current methods. It also highlights the ongoing need on the part of historians to approach contemporary sources critically, informed by sources produced and debated in the pre-genocide period. Résumé: Depuis 1994, le Président Paul Kagame et son parti politique, le Front Patriotique Rwandais, ont poussé pour une politique d'intégration nationale basée sur une version simplifiée de l'histoire du Rwanda apte à estomper les tensions ethniques qui aboutirent au génocide de 1994. Il en a découlé une politisation accrue de l'histoire du Rwanda, au sein d'une palette de versions divergentes du passé racontées dans des contextes privés, dont le message était de faire partager aux Rwandais leurs expériences du génocide. Cet article illustre les représentations divergentes de certaines figures monarchiques, souvent innominées, auxquels les narrateurs attribuent des valeurs suivant leur affiliation politique, leur expériences de vie et leur identité. Ces récits témoignent des nombreuses voies à travers lesquelles les Rwandais d'aujourd'hui racontent leurs expériences de l'histoire en réponse à l'histoire officielle du Rwanda ainsi qu'aux versions officielles précédentes. Une analyse attentive en dit beaucoup de l'ambiance politique dans le Rwanda du post-génocide; en particulier, elle montre que les Rwandais continuent de considérer le passé de la nation à travers des perspectives différentes, ce qui montre l'énorme défis du gouvernement rwandais, dont le but est de réconcilier la population suivant ses démarches actuelles. L'article éclaire aussi le besoin courant des historiens d'approcher d'une manière critique les sources contemporaines à travers des sources produites et débattues avant le génocide.